2000
DOI: 10.1210/jcem.85.1.6250
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Fluctuations of Serum Estradiol Levels Influence Biochemical Markers of Bone Resorption in Young Women

Abstract: We investigated the effect of physiologic variations in sex hormone levels during the menstrual cycle on biomarkers of bone turnover. Blood and 24-h and fasting urine samples were obtained in nine women (age, 25.1+/-3.0 yr) with regular menstrual cycles during the early follicular period (t1), 3 days before ovulation (t2), 3 days after ovulation (t3), at the midluteal period (t4) and again during the early follicular period of the next cycle (t5). All subjects had a calcium intake covering current dietary reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 32 publications
8
66
1
2
Order By: Relevance
“…Similar results were also observed by other authors [22,25]. The raised estrogen levels possibly by acting through parathyroid hormone could be responsible for depicting the body stores of magnesium by decreasing the reabsorption of magnesium ions by the renal tubules thus resulting in midcycle decline 29 . In Table- 30,31 .…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also observed by other authors [22,25]. The raised estrogen levels possibly by acting through parathyroid hormone could be responsible for depicting the body stores of magnesium by decreasing the reabsorption of magnesium ions by the renal tubules thus resulting in midcycle decline 29 . In Table- 30,31 .…”
Section: Discussionsupporting
confidence: 89%
“…Biochemical markers of bone resorption are clearly influenced by fluctuations in these hormones [10,23,48]. In one study, PYD varied as much as 50% from 3 days after ovulation to day 3 of the follicular period of the same menstrual cycle [48]. Because menstrual cycles were not controlled for in the present study, this variability with sex hormone fluctuations (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Much of the variability is likely to be related to cyclic fluctuations of female sex hormones. Biochemical markers of bone resorption are clearly influenced by fluctuations in these hormones [10,23,48]. In one study, PYD varied as much as 50% from 3 days after ovulation to day 3 of the follicular period of the same menstrual cycle [48].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of serum magnesium in present study were significantly highest during the luteal phase and lowest during the follicular phase. The raised estrogen levels possibly by acting through parathyroid hormone could be responsible for depicting the body stores of magnesium by decreasing the reabsorption of magnesium ions by the renal tubules thus resulting in midcycle decline 5 . Therefore, it is suggested that calcium/magnesium ratio may be related to the premenstrual syndrome complaints that some women have during this period 34 .…”
Section: Discussionmentioning
confidence: 99%